Performance analysis of ANN based YCbCr skin detection algorithm - Aibinu, Abiodun Musa; Shafie, Amir Akramin; Salami, Momoh Jimoh Emiyoka (Elsevier, 2012)
system. The performance analysis of artificial neural network based –YcbCr skin recognition and three other techniques is evaluated in this work. Results obtained show that the use of YCbCr color model performs better than RGB colour model and the use of artificial neural network further improves the accuracy of the system. © 2012 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the Centre of Humanoid Robots and Bio-Sensor (HuRoBs), Faculty of Mechanical Engineering, Universiti Teknologi MARA.